1998
DOI: 10.1103/physrevb.58.5287
|View full text |Cite
|
Sign up to set email alerts
|

Evolution towards centrosymmetry of the nonlinear-optical materialRbTiOPO4in the temperature range 293–973 K: Alkaline displacements and titanyl deformations

Abstract: The crystal structure of rubidium titanyl phosphate, RbTiOPO 4 ͑space group Pna2 1 ͒, has been refined at room temperature, and at 473, 673, 873, and 973 K, by using single-crystal x-ray-diffraction techniques. The data show a large anharmonic motion of the rubidium ions increasing with temperature. To describe the importance of this motion in the phase-transition procedure and in the ionic conductivity phenomenon, two models are developed. The study of the deviation to the centrosymmetric structure ͑space gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 25 publications
5
25
0
Order By: Relevance
“…8 The second, much broader CP in KTP ͑more than 150 GHz͒ was attributed to relaxation dynamics of an on site moving nature. 8 The third CP, observed only in a few Kelvin range in the Brillouin study of RbTiOPO 4 , was attributed to coupling of the soft mode to a relaxator. 26 In our case, the observed CPs are related to the phase transitions but the origin of CP in the tetragonal phase cannot be explained by bilinear coupling of the soft optic mode to the diffusive mode since CP relates to a different symmetry ͑E͒ than the diffusive mode ͑A 2 ͒.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…8 The second, much broader CP in KTP ͑more than 150 GHz͒ was attributed to relaxation dynamics of an on site moving nature. 8 The third CP, observed only in a few Kelvin range in the Brillouin study of RbTiOPO 4 , was attributed to coupling of the soft mode to a relaxator. 26 In our case, the observed CPs are related to the phase transitions but the origin of CP in the tetragonal phase cannot be explained by bilinear coupling of the soft optic mode to the diffusive mode since CP relates to a different symmetry ͑E͒ than the diffusive mode ͑A 2 ͒.…”
mentioning
confidence: 99%
“…[1][2][3] Many measurements demonstrated that it undergoes a second-order displacive phase transition at 1206 K. [4][5][6][7] However, Raman studies suggested that the phase transition is induced by the diffusive mode. 8 Later studies showed that replacement of Ti IV ͑PO 4 3− ͒ ions by Ge IV , Sn IV , Fe III , or Nb V ͑AsO 4 3− or GeO 4 4− ͒ ions has a significant impact on the phase transition mechanism and properties of KTP isomorphs. [9][10][11] For instance, it was shown that the phase transition in germanate analogs of KTP is both displacive and order-disorder types, 10 whereas the phase transition in KFeFPO 4 is closer to order-disorder type than to displacive.…”
mentioning
confidence: 99%
See 3 more Smart Citations